Metagenomic Identification of Bacterioplankton Taxa and Pathways Involved in Microcystin Degradation in Lake Erie - Mou, Xiaozhen (Public Library of Science, 2013)
Cyanobacterial harmful blooms (CyanoHABs) that produce microcystins are appearing in an increasing number of freshwater ecosystems worldwide, damaging quality of water for use by human and aquatic life. Heterotrophic bacteria assemblages are thought to be important in transforming and detoxifying microcystins in natural environments. However, little is known about their taxonomic composition or pathways involved in the process. To address this knowledge gap, we compared the metagenomes of Lake Erie free-living bacterioplankton assemblages in laboratory microcosms amended with microcystins relative to unamended controls. A diverse array of bacterial phyla were responsive to elevated supply of microcystins, including Acidobacteria, Actinobacteria, Bacteroidetes, Planctomycetes, Proteobacteria of the alpha, beta, gamma, delta and epsilon subdivisions and Verrucomicrobia. At more detailed taxonomic levels, Methylophilales (mainly in genus Methylotenera) and Burkholderiales (mainly in genera Bordetella, Burkholderia, Cupriavidus, Polaromonas, Ralstonia, Polynucleobacter and Variovorax) of Betaproteobacteria were suggested to be more important in microcystin degradation than Sphingomonadales of Alphaproteobacteria. The latter taxa were previously thought to be major microcystin degraders. Homologs to known microcystin-degrading genes (mlr) were not overrepresented in microcystin-amended metagenomes, indicating that Lake Erie bacterioplankton might employ alternative genes and/or pathways in microcystin degradation. Genes for xenobiotic metabolism were overrepresented in microcystin-amended microcosms, suggesting they are important in bacterial degradation of microcystin, a phenomenon that has been identified previously only in eukaryotic systems.